Strategic analysis of long term with swot and QSPM methods (case study at fatabarfarm in grobogan) - Tiya Pratiwi, Florentina Ajeng; Wulandari, Wulandari; Utama, Juventius Wahyu; Widyaningtya, Dian Prasetyo; Dito, Anoki Herdian; Maranata, Bonaventura Hendrawan (Institute of Computer Science (IOCS), 2025)
This study aims to examine one of the MSMEs (Micro, Small, and Medium Enterprises) of Fatabar Farm, which operates in the goat farming sector in the Grobogan area. The research seeks to reevaluate its develop a structured long-term strategy for its business operations. The objective of this research is to determine the most appropriate strategy by analyzing the long-term strategy using SWOT analysis and the QSPM matrix. This approach aims to formulate new strategies that enhance the competitive advantage of the livestock business. The methods used include SWOT analysis and the QSPM, comprising several steps such as the IFAS matrix, EFAS matrix, IE matrix, IE combination matrix, and QSPM. The research was conducted using qualitative methods, including interviews and observations at Fatabar Farm in Grobogan. The results of the IFAS and EFAS matrices indicate that Fatabar Farm’s SWOT analysis is above average, as evidenced by an IFAS final score of approximately 2.92 and an EFAS final score of 3.42. The IE matrix also shows that the company is positioned in Cell II, which signifies a